1999
DOI: 10.1523/jneurosci.19-13-05449.1999
|View full text |Cite
|
Sign up to set email alerts
|

Different Proctolin Neurons Elicit Distinct Motor Patterns from a Multifunctional Neuronal Network

Abstract: Distinct motor patterns are selected from a multifunctional neuronal network by activation of different modulatory projection neurons. Subsets of these projection neurons can contain the same neuromodulator(s), yet little is known about the relative influence of such neurons on network activity. We have addressed this issue in the stomatogastric nervous system of the crab Cancer borealis. Within this system, there is a neuronal network in the stomatogastric ganglion (STG) that produces many versions of the pyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
171
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(172 citation statements)
references
References 67 publications
(109 reference statements)
1
171
0
Order By: Relevance
“…Previous work showed that the VCN mechanosensory system influences at least four CoG projection neurons . All four of these neurons have synaptic actions on gastric mill neurons Norris et al, 1994Norris et al, , 1996Blitz et al, 1999). In the current study we demonstrate that, despite these relatively widespread VCN actions, the conjoint activity of MCN1 and CPN2 is necessary and likely sufficient to mediate the VCN-elicited gastric mill rhythm.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Previous work showed that the VCN mechanosensory system influences at least four CoG projection neurons . All four of these neurons have synaptic actions on gastric mill neurons Norris et al, 1994Norris et al, , 1996Blitz et al, 1999). In the current study we demonstrate that, despite these relatively widespread VCN actions, the conjoint activity of MCN1 and CPN2 is necessary and likely sufficient to mediate the VCN-elicited gastric mill rhythm.…”
Section: Discussionmentioning
confidence: 51%
“…At the onset of each experiment the neurons were identified by using routine methods described previously (Beenhakker et al, 2004). Briefly, neurons were identified by their patterns of activity, interactions with other neurons, and axonal branching patterns (Weimann et al, 1991;Norris et al, 1994;Blitz and Nusbaum, 1997;Blitz et al, 1999). All but one gastric mill circuit neuron [interneuron 1 (Int1] in the STG are also motor neurons that project via the posterior STG nerves to innervate their target muscles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One strategy of achieving specificity in this modulation is the colocalization of peptides with classic transmitters and the release of distinct cotransmitter complements (Blitz et al, 1999;Wood et al, 2000) (for review, see Nusbaum et al, 2001). Another strategy of achieving specificity in peptidergic actions is the axon typespecific modulation of the efficacy of discharge patterns of motor neurons at the target cells.…”
Section: Functional Significance Of Differential Peptidergic Modulationmentioning
confidence: 99%